Dynamic alterations of functional connectivity and amplitude of low-frequency fluctuations in patients with unilateral sudden sensorineural hearing loss. (16th February 2022) - Li, Yu-Ting; Chen, Jia-Wei; Yan, Lin-Feng; Hu, Bo; Chen, Tian-Qi; Chen, Zhu-Hong; Sun, Jing-Ting; Shang, Yu-Xuan; Lu, Lian-Jun; Cui, Guang-Bin; Wang, Wen
Highlights: Our research identified two recurring states in SSNHL patients and HC. A more frequent state characterized by generally sparse, and a less frequent state characterized by widespread close connectivity. SSNHL patients preferred to staying in the sparse functional connectivity compared with HC. SSNHL patients displayed reduced dALFF value, which represent dynamic neuronal activity, in the visual areas. The dynamic neuroimaging indicator was correlated with endogenous coagulation function in SSNHL patients. Abstract: Unilateral sudden sensorineural hearing loss (SSNHL) adversely affects the quality of life, leading to increased risk of depression and cognitive decline. Our previous studies have mainly focused on the static brain function abnormalities in SSNHL patients. However, the dynamic features of brain activity in SSNHL patients are not elucidated. To explore the dynamic brain functional alterations in SSNHL patients, age- and sex- matched SSNHL patients (n = 38) and healthy controls (HC, n = 44) were enrolled. The dynamic functional connectivity (dFC) and dynamic amplitude of low-frequency fluctuation (dALFF) methods were used to compare the temporal features and dynamic neural activity between the two groups. In dFC analyses, the multiple functional connectivities (FCs) were clustered into 2 different states; a greater proportion of FCs in SSNHL patients showed sparse state compared with HC. In dALFF analyses, SSNHL individuals exhibited decreased dALFF variability in bilateral inferior occipital gyrus, middle occipital gyrus, calcarine, right lingual gyrus, and right fusiform gyrus. dALFF variability showed a negative correlation with activated partial thromboplatin time. The dynamic characteristics of SSNHL patients were different from static functional connectivity and static amplitude of low-frequency fluctuation, especially within the visual cortices. These findings suggest that SSNHL patients experience cross-modal plasticity and visual compensation, which may be closely related to the pathophysiology of SSNHL.